Feral Hues & Invasive Pigments: Examining nature-based solutions through ecosocial art engaging spontaneous urban vegetation and informal greenspace - Ellie Irons (Nature-Based Solutions)
The project Feral Hues and Invasive Pigments (FH&IP) addresses the role of spontaneous urban plants (aka weeds) through ecosocial art, with the goal of reducing human alienation from plant life and land in urban and disturbed habitats. Hands-on work with spontaneous urban plants through ecosocial artistic methods—like walks, workshops, and land-based sculptures—provides cues for understanding weedy plants and informal greenspace (IGS) as part of nature-based solutions (NBS) in cities. In dialog with NBS research that takes a justice-oriented, degrowth approach to urban greenspace, the FH&IP project invites hands-on, hyperlocal participation of humans and plants at the neighborhood level to enhance the role of low maintenance IGS. Bringing ecosocial artistic methods into conversation with NBS research is one way to open up knowledge practices that inform both fields. Multisensorial, direct engagement with urban-dwelling plants can help practitioners and participants understand what kinds of maintenance and tending might help improve sentiment around spontaneous urban vegetation and improve its functional benefits for human communities. In the right context, such benefits range from flood mitigation to improved mental health to cooler, cleaner air. A “ladder of engagement” for reciprocal exchange with spontaneous urban plants is proposed to trace how the ecosocial artistic methods employed in FH&IP build plant-human solidarity towards more functional NBS in IGS. Methods like gallery installations, workshops, and walks are described and analyzed for their strengths and weaknesses in accessibility and depth, qualities that help initiate engagement and move participants up the ladder. At the lowest rung of the ladder, participants ignore or actively harm spontaneous urban plants, then move to noticing, tending, and eventually advocating for plants and the land they dwell on. The shift from alienation to advocacy has potential to improve the function of IGS by amplifying and enhancing contextually appropriate NBS that respect local needs and desires while improving equitable distribution of bioculturally diverse greenspace.